Interest of Community in Using Silk Fabric in Soppeng Regency South Sulawesi - Nurhaedah Muin; Nur Hayati (Buletin Eboni, 2019)
Silk fabric is one of the natural silk products of the commodity Non-Timber Forest Products that the people of South Sulawesi are cultivating as a source of the family economy. People of Soppeng Regency have cultivated silkworms to produce cocoons which are then processed into yarn and fabric. Besides, they are also a user. Advances in technology and information also influence people's clothing choices, not least in Soppeng Regency. The interest of the community in seeking raw materials as well as users of natural silk products will affect the sustainability of the business. This paper aimed to find out people's interest in silk fabric, influencing factors and conservation efforts in Soppeng Regency, South Sulawesi. The study used a quantitative descriptive method by collecting data through observation and interviews with 30 respondents. The results showed that 70 percent of the people were still interested in silk when attending official events, 23 percent of respondents chose the use of silk fabric  in the form of sarong, the reason for using silk fabric because of prestige or pride and cultural factors, 70 percent of respondents prefer to buy mixed silk or not original, the purchase of pure silk fabric is rarely done because the price is expensive and there are many choices of clothing materials with affordable prices. For this reason, the government needs to motivate the use of silk fabric in South Sulawesi in the form of local regulations as an effort to preserve the culture and maintain business continuity along with optimizing the supporting factors of cocoon and silk yarn production so that the economy and people's purchasing power can be increased.